The standardised structure of German indictments and the particularities of their translation into Bulgarian - Kileva-Stamenova, Reneta (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
Based on relevant theoretical approaches to legal translation, the article deals with the problems of translating indictments from German into Bulgarian. The focus is on the conventionalised framework structure of this type of text in both legal systems, which is subjected to an interlingual comparison. The insights gained from this are taken into account, along with other criteria, in the production of two sample translations into Bulgarian – of the frame structure of the North German and the frame structure of the South German variant of the indictment. The article concludes with a commentary on the sample translations and their applicability in translator training and for translation practice.